2013
DOI: 10.1111/ddi.12033
|View full text |Cite
|
Sign up to set email alerts
|

Rare or elusive? A test of expert knowledge about rarity of Amazon forest birds

Abstract: Aim To offer a test of expert knowledge about rarity of twenty Amazon forest bird species following an approach that equates rarity with low site occupancy and formally accounts for imperfect species detection. We define ten pairs of closely related species, each pair with one hypothetically common and one hypothetically rare species. Our null hypothesis is that members of each pair have similar occupancy, with hypothesized differences due to detection errors alone.Location A 1000-ha plot of primary rainforest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Even if observers could stay in the field 24 hr/d throughout the year, there would still be a problem of observer bias (Cerqueira et al, in press). This is a major limitation especially when it is necessary to sample many sites simultaneously or when data are collected over many years by many different observers.…”
Section: Discussionmentioning
confidence: 99%
“…Even if observers could stay in the field 24 hr/d throughout the year, there would still be a problem of observer bias (Cerqueira et al, in press). This is a major limitation especially when it is necessary to sample many sites simultaneously or when data are collected over many years by many different observers.…”
Section: Discussionmentioning
confidence: 99%
“…Past studies have found experts to possess useful knowledge for conservation decision‐making in the absence of empirical information, but to also be less accurate than models developed from empirical data (e.g. Cerqueira et al ., ; McConnachie & Cowling, ; Aizpurua et al ., ; Drolet et al ., ), which could be seen in the variation of the responses of individual experts in our study. Though not significant, the negative association observed here between experts’ expectations of their knowledge and actual performance reflects a common finding in studies assessing expert performance (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 69 interviews were conducted involving 207 people; participants were interviewed together in groups in some instances. Although data collected from local knowledge can be comparable to those collected using conventional methods (Danielson et al 2005, Jones et al 2008, Parry and Peres 2015), the characteristics of observers such as age (Turvey et al 2010) and experience (Cerqueira et al 2013) can influence ability to detect a species accurately. The sampling approach meant that all participants were men, as they were considered to have greater direct experience of parrot behaviour and ecology, since within local culture they typically spend a much greater proportion of their time engaged in activities in forested areas, and traditionally only men trap parrots.…”
Section: Methodsmentioning
confidence: 99%